Investigation of the prevalence and role of mobile genetic elements associated with an aminoglycoside resistance gene, aacC2a, in Acinetobacter baumannii - Jongwe, Tsungai Ivai (Division of Medical Microbiology, 2014)
Includes abstract. Includes bibliographical references (leaves 115-141).